2021
DOI: 10.1177/1071181321651065
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Camera Computer Vision-Based Method for 3D L5/S1 MomentEstimation During Lifting Tasks

Abstract: Excessive low back joint loading during material handling tasks is considered a critical risk factor of musculoskeletal disorders (MSD). Therefore, it is necessary to understand the low-back joint loading during manual material handling to prevent low-back injuries. Recently, computer vision-based pose reconstruction methods have shown the potential in human kinematics and kinetics analysis. This study performed L5/S1 joint moment estimation by combining VideoPose3D, an open-source pose reconstruction library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Second, we admit that the reconstructed body pose through VideoPose3D, which is used to calculate the reference point of operation position, may carry errors. A previous study showed that the joint location error due to computer-vision algorithm is around 7.7% (Wang et al, 2021). For a more precise validation, a laboratory- grade motion tracking system would be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we admit that the reconstructed body pose through VideoPose3D, which is used to calculate the reference point of operation position, may carry errors. A previous study showed that the joint location error due to computer-vision algorithm is around 7.7% (Wang et al, 2021). For a more precise validation, a laboratory- grade motion tracking system would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Martinez (2017), human motion was well reconstructed using a simple and lightweight deep neural network. The fast-developing machine learning methods appear to be capable to form a more efficient way of understanding and improving workers’ postures (Li, et al, 2020; Wang et al, 2021). However, computer vision-aided posture assessment heavily relies on the workplace configuration and hardware.…”
Section: Introductionmentioning
confidence: 99%